Kepastian Hukum dalam Pemberian dan Pembatalan Hak Guna Usaha di Kawasan Hutan Berdasarkan Pasal 21 dan 23 UU Pokok Agraria Tahun 1960 (UUPA): Penelitian - Rismahayani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Right to Cultivate (HGU) over state land, particularly in forest areas, has become a major polemic in natural resource management in Indonesia. Since the reformation, the granting of HGU for oil palm plantations has grown rapidly; according to the Ministry of Environment and Forestry (KLHK) (2024), the HGU area reached 9.26 million hectares, with 795,000 hectares located in forest areas. HGU is regulated in Articles 21 and 23 of the 1960 UUPA and can only be issued after the forest area has been officially designated and/or released by the Minister of KLHK. However, Constitutional Court Decision No. 45/PUU-IX/2011 stated that the designation of forest areas is invalid without legal certainty, confirmed boundaries, and public involvement. Agrarian conflicts often arise due to inconsistencies between the Agrarian and Forestry Laws. This study analyzes the legal certainty in the granting and revocation of HGU in forest areas. Using a normative juridical approach and case studies, it was found that HGU certificates are valid until officially revoked or through a final court decision. HGU can only be issued after the release of forest areas; Otherwise, the HGU will be null and void by law and may be subject to criminal sanctions in accordance with Law 18/2013.